Perbandingan Kebutuhan Pergantian Pelat dari Hasil Marking dengan Aktual dan Banyaknya Elektroda yang Dibutuhkan pada Bottom Kapal TK. Pegasus 5 - Langgeng, Diana (Marine Science and Technology Journal; Vol 3 No 1 (2022): Marine Science and Technology Journal, 2022)
Every ship's plate will experience thinning or wear due to several factors, thinning of the plate is normal, especially at the bottom of the waterline. Therefore it is necessary to hold maintenance and replating on each part of the ship on a regular basis. Therefore, it is necessary to analyze the plate requirement at the change of the barge plate and how many electrodes are used. The purpose of this study is to determine the estimation of plate requirements based on marking, to find out the difference between the comparison between marking and actual plate requirements, and to determine the needs of electrodes in the process of replacing TK plates. Pegasus 5. Which is used as a reference for determining material so as not to suffer losses and to achieve the effectiveness and efficiency of material use. This research is a quantitative research, in this study there are several variables. Based on the research objectives, the results obtained for the estimation of the use of plates for the replating bottom of the Pegasus 5 barge as many as 10 sheets with a plate size of 6096 x 1828 and a thickness of 12 mm. With a comparison difference of 7.7%, and the number of electrodes needed is 236.032 kg or 48 packs.